PENERAPAN TEACHING AT THE RIGHT LEVEL (TARL) UNTUK MENGATASI KESULITAN BELAJAR PESERTA DIDIK KELAS XI K SMA N 6 SEMARANG PADA MATA PELAJARAN BAHASA INDONESIA MATERI KARYA TULIS ILMIAH - Fita Dwi Damayanti; Turahmat; Oktarina Puspita Wardani (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
ABSTRACT Many students at the Senior High School (SMA) level face obstacles in understanding and compiling Scientific Papers (KTI). These difficulties include understanding the structure of the text, using scientific language, to writing citations and bibliographies. The Teaching at the Right Level (TaRL) approach is present as an innovative strategy to overcome these challenges. TaRL emphasizes the importance of aligning the learning process with the level of ability of students, not only based on class level. This study describes how the application of TaRL in class XI K of SMA Negeri 6 Semarang can improve students' understanding and skills in writing Scientific Papers through initial assessments, grouping based on ability levels, and the use of differentiated learning strategies. Keywords: TaRL, Scientific Papers, learning, learning difficulties, SMA.